Review on Autoimmune Reactions in Female Infertility: Antibodies to Follicle Stimulating Hormone. (5th October 2011) - Haller-Kikkatalo, Kadri; Salumets, Andres; Uibo, Raivo
Abstract : Female fertility can be affected by diseases or dysfunctions of reproductive tract, neuroendocrine system, and immune system. Reproductive autoimmune failure can be associated with overall activation of immune system or with immune system reactions specifically directed against ovarian antigens. Majority of the antiovarian autoantibodies are directed against β -subunit of follicle stimulating hormone (anti-FSH). This paper summarizes a current clinical classification of female infertility in the context of general activation of autoimmunity and antiovarian autoimmunity by describing serum anti-FSH. The presence of naturally occurring anti-FSH in healthy women will be discussed. In addition, the putative impairment of ovarian folliculogenesis in case of increased production of those antibodies in infertile women will be characterized.